On the design of criminal trials: The benefit of three-verdict systems - Ron Siegel; Bruno Strulovici (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2015)
We propose adding a third,intermediate,verdict to the two-verdict used in criminal trials. We show that the additional verdict can be used to distinguish between convicted defendants, based on the residual doubt regarding their guilt at the end of the trial, in a way that improves welfare and does not increase the set of innocent defendants who are wrongly convicted.It can also be guaranteed that wrongfully convicted defendants do not serve longer sentences, provided that the sentence in the two-verdict system was not too inefficiently low. Since even acquitted defendants may face a social stigma, we also consider using the additional verdict to distinguish between acquitted defendants, and provide conditions under which this improves welfare.Generalizations to multi-verdict systems with a larger number of verdicts are also explored. We also consider plea bargains, and show that a properly chosen plea in a two-verdict system leads to higher welfare than any multi-verdict system, and is in fact the optimal mechanism. Finally, we consider the impact of multiple verdicts on the incentives to gather evidence, and show that the effect is generally positive.
Keywords: 330